2015
DOI: 10.4103/2229-516x.157170
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of metabolic syndrome in type 2 diabetes mellitus patients

Abstract: Background:The diabetic condition is influenced by several factors, some of which can accelerate the disease's progression to various complications that aggravate the morbidity.Aims:This study aimed at determining the prevalence of metabolic syndrome (MetS) and its individual components and the most critical predictive risk factors of MetS in type 2 diabetic patients.Materials and Methods:This cross-sectional study involved 150 type 2 diabetes mellitus patients and was conducted at the Diabetes Centre of the K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
72
6
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(102 citation statements)
references
References 17 publications
21
72
6
3
Order By: Relevance
“…[11][12] Similar study done at diabetes centre in Galle, Sri Lanka showed the prevalence of metabolic syndrome in Type 2 DM population to be 70% which was consistent with our study. 13 Our study showed 84 male and 58 female participants had metabolic syndrome which was not similar to the study by Ford et al 4 and Nsiah K et al 14 which showed higher prevalence of metabolic syndrome in females. This variation may be due to less number of female patients who approached for hospital services during the study period.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…[11][12] Similar study done at diabetes centre in Galle, Sri Lanka showed the prevalence of metabolic syndrome in Type 2 DM population to be 70% which was consistent with our study. 13 Our study showed 84 male and 58 female participants had metabolic syndrome which was not similar to the study by Ford et al 4 and Nsiah K et al 14 which showed higher prevalence of metabolic syndrome in females. This variation may be due to less number of female patients who approached for hospital services during the study period.…”
Section: Discussioncontrasting
confidence: 63%
“…Similar result was seen in the study done at regional diabetes centre in Galle, Southern Sri Lanka, which showed raised waist circumference as an important predictor for metabolic syndrome defined by all three World Health Organisation (WHO), NCEP-ATP III, and International Diabetes Federation (IDF). 13 adiposity, and an increasing number of studies are reporting strong associations between WC, visceral adipose tissue, and obesity-related health risks. 15 Hepatic production of very low density lipoprotein with consequent release of high TGR in blood is associated with insulin resistance resulting from central obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies like Val FK et al and Nsiah K et al showed lower prevalence of 55.9% and 58% respectively. 22,23 The prevalence of metabolic syndrome among non-diabetics was considerably very low (7.2%) and the results were significant (p-value=0.0001).…”
mentioning
confidence: 91%
“…Type II diabetes is increasing worldwide with upwards of 58% of patients with diabetes developing the metabolic syndrome [1]. Early interventions and screening in individuals with pre-diabetes has been shown to decrease the risk of developing diabetes [2].…”
Section: Introductionmentioning
confidence: 99%